NEW ABOUT THE INITIAL STAGES OF EMBRYONIC HUMAN DEVELOPMENT - Додонов, Максим Владимирович; Артымук, Дмитрий Анатольевич (Mother and Baby in Kuzbass, 2018)
The objective of the study was to up-date the information on the initial stages of human embryonic development to the stage of blastocyst. Methodology of the study. We used databases: Cochrane, Medline, PubMed, HINARY. The search words were: «initial stages of human embryonic development». The depth of the search was 7 years (2012-2018). Results and discussion. 426 publications (1977-2018) were found out. 112 publications corresponded to the search criteria from 2012 to 2018 years. Understanding human pre-implantation development has important implications for assisted reproductive technology and for human embryonic stem cell-based therapies and treatment of oncological diseases. Owing to limited resources, the cellular and molecular mechanisms governing this early stage of human development are poorly understood. Nonetheless, recent advances in non-invasive imaging techniques and molecular and genomic technologies have helped to increase our understanding of this fascinating stage of human development. Conclusions. At the present time, humanity has come close to understanding the embryonic development to the blastocyst stage. A detailed understanding of the process of embryogenesis is necessary to solve, first of all, clinical problems: treatment of oncological diseases and infertility. However, most researchers advocate preventing any application of genome editing on the human germline until after a rigorous and thorough evaluation and discussion are undertaken by the global research and ethics communities.